A Comparison of Automobile Demand Equations - Hess, Alan C. (Econometrica, 1977)
This paper reports the testing of hypotheses concerning: (i) whether the household is better viewed as planning over a single-period versus a multiperiod horizon; (ii) whether the household is better viewed as planning in a single-asset or a multiasset framework; (iii) the relative importance of substitution and wealth effects as sources of change in the stock demand for automobiles. The findings are that a multiperiod, multiasset model best describes stock demand, that the separation theorem which implies a zero wealth effect is rejected, and that substitution effects are seven times more important than wealth effects. THE ECONOMIC LITERATURE CONTAINS several empirical studies of household automobile demand [3, 7, 8, and 10] and theoretical models of the household [1, 4, 5, 6, and 14] which are or could be applied to automobile demand. Two aspects of theory which are not fully reflected in the empirical studies are the implications of a multiperiod horizon and the possibility of substitution among assets. Theoretical models [5 and 15] which assume a multiperiod horizon imply that relevant asset prices are user costs and the appropriate constraint is wealth. In contrast, most empirical studies use purchase prices rather than user costs, and income rather than wealth. In addition, theoretical models [4 and 5] permit substitution over a variety of goods, whereas most empirical studies restrict substitutions to automobiles and consumption goods. To the extent that estimated equations are misspecified, the prevailing conclusion that income effects are more important than substitution effects may be due to left-out-variable bias. This paper investigates each of these three issues-the length of the horizon, the range of substitutions, and the relative importance of substitution and wealth effects-by estimating over the same set of data a variety of alternative equations which reflect different assumptions about the horizon and range of substitutions. Initially, a multiperiod, multiasset model of the household consumption-saving decision is stated and used to derive the appropriate arguments for the broadest estimating equation. A linear approximation of this equation is estimated using quarterly United States data covering the years 1952-1972. Then this estimate is compared to competing equations derived under restrictions on the multiperiod, multiasset model. Specifically, demand equations derived under multiperiod, single-asset, single-period, single-asset, and single-period, multiasset assumptions are estimated and compared to the broadest multiperiod, multiasset equation. In addition, versions of the restricted equations which have appeared in the literature are estimated and compared. The findings are: (i) a multiperiod, multiasset equation best describes automobile stock demand, (ii) estimates of substitution and wealth effects are quite sensitive to specification bias, and (iii) substitution effects are seven times more important than wealth effects in the dominant equation.